2009
DOI: 10.1111/j.1462-5822.2009.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Serine-71 phosphorylation of Rac1/Cdc42 diminishes the pathogenic effect ofClostridium difficiletoxin A

Abstract: SummaryClostridium difficile toxin A and B (TcdA/TcdB) are glucosyltransferases that glucosylate GTPases of the Rho family. The epidermal growth factor (EGF) positively modulates C. difficile toxin-induced disturbance of the intestinal barrier function by an unknown mechanism. We found that EGF-treated CaCo-2 monolayers were less susceptible to TcdA-catalysed glucosylation of Rac1 but not of RhoA, which correlated with phosphorylation of Rac1 at Ser-71. Phospho-Rac1/phospho-Cdc42 (Ser-71) still bound to the PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
1
46
1
1
Order By: Relevance
“…33 Both TcdA and TcdB are cytotoxic and trigger inflammatory responses, causing disruption of the actin cytoskeleton of intestinal epithelial cells and disrupting tight junctions. 34,35 In this study we confirmed the essential role of these toxins in mediating colitis as no clinical or histopathologic disease was seen in animals that were challenged with the non-toxigenic strain F200. However, the fact that this strain could colonize to a level equivalent of a fully toxigenic strain demonstrates that toxin A and toxin B are not required to establish C. difficile colonization.…”
Section: Discussionsupporting
confidence: 67%
“…33 Both TcdA and TcdB are cytotoxic and trigger inflammatory responses, causing disruption of the actin cytoskeleton of intestinal epithelial cells and disrupting tight junctions. 34,35 In this study we confirmed the essential role of these toxins in mediating colitis as no clinical or histopathologic disease was seen in animals that were challenged with the non-toxigenic strain F200. However, the fact that this strain could colonize to a level equivalent of a fully toxigenic strain demonstrates that toxin A and toxin B are not required to establish C. difficile colonization.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, a similar mechanism was reported for Rac1: Thr108 is phosphorylated by ERK in response to EGF, which alters the interaction of Rac1 with PLC-γ1, affecting cell migration (29). Rac1 may also be phosphorylated by the Akt kinase at Ser71, which results in reduced GTP-binding without affecting GTPase activity (14,30). Previous studies reported a PKG recognition site in Rac1, suggesting that Rac1 may be directly phosphorylated by PKG II (27); however, the results of the present study found no evidence of this interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence indicates that phosphorylation may be an important mechanism for the regulation of Rac1 activation (12,14). Phosphorylation of Rac1 at Ser71 has been reported to modulate downstream signaling by inhibiting the interaction of Rac1 with its effectors (12).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, very recent data showed that Rac1 phosphorylated at S-71 by Akt kinase remained in its GTP-bound conformation as proven by pulldown assays using the PAK-CRIB domain. 52 In the latter study, phosphorylation at S-71 did not only fail to inactivate Rac1 but interfered with recognition of Rac1 by glucosylating bacterial toxins such as TcdA from Clostridium difficile. Both aspects resulted in a protective effect against disturbance of colonic barrier functions induced by clostridial glucosylating toxins.…”
mentioning
confidence: 99%
“…Interestingly, the S-71 site is conserved in another member of this Rho family GTPases, Cdc42, which can also undergo phosphorylation. 52 Since both of these GTPases are targets for a variety of microbial virulence factors and crucial for both invasive and non-invasive bacteria, phosphorylation of Rac1/Cdc42 at S-71 could therefore be of general importance in bacterial-host interactions. Future studies should also examine pathogeninduced alteration on the three groups of regulatory proteins in the Rho GTPase cycle: the guanine dissociation inhibitors (GDIs), the guanine nucleotide exchange factors (GEFs), and GTPase-activating proteins (GAPs).…”
mentioning
confidence: 99%